La Educación bilingüe y el desarrollo de la identidad cultural en los estudiantes de tercero de bachillerato de la Unidad Educativa Intercultural Bilingüe “Monseñor Leonidas Proaño”, Riobamba 2022 - Quishpi Caiza, María Alicia (2022)
ABSTRACT: In this research work, the theme "bilingual education and the development of cultural identity in third-year high school students of the "Monseñor Leonidas Proaño" bilingual intercultural educational unit, Riobamba 2022, is developed. At present, the deficit in bilingual and intercultural education is evident, this originates from the lack of cultural identity from the childhood education that is born in the homes of each student, however, in Ecuador an interest in the different institutions is observed education so that there is a strengthening of cultural identity in the different ethnic groups and nationalities that are within the nation. In order to obtain data on the growth and interest that bilingual education and cultural identity have, a methodology is used both in the field and in the bibliography, through field work; information is collected from the high school students of the educational unit. The population with which he interacted was 15 students, who represented all the students of parallel "A". With the results that were obtained after the application of the survey, it can be evidenced that only a percentage that is within the normal parameters is clear about bilingual education and the cultural identity that each one of them has; For this reason, it was concluded that there should be more support from both national and local authorities and from the educational institution to reform this side of education in Ecuador. Keywords: Bilingual Education, Cultural Identity, Intercultural, Ethnicity.